Sodium Methoxide Catalyzed Preparation of Nitrogen Compounds from Palm Oil Methyl Esters as Corrosion Inhibitor - Ilim; Hidayah, Laila; Yuliyanda, Devi; Delilawati Pandiangan, Kamisah; Simanjuntak, Wasinton (Science and Technology Indonesia, 2024)
This research was conducted to study preparation of nitrogen compounds by reacting palm oil derived methyl esters and diethanolamine using sodium methoxide as a catalyst. The chemical composition of the product was analyzed using the gas chromatography-mass spectrometry (GC-MS) method. The product was then applied as a corrosion inhibitor for mild steel in CO2 saturated 3% NaCl solution. Experimental results indicate that the reaction product contains six nitrogen compounds with a relative percentage of 63.7%, and the rest 36.7% are a mixture of unreacted diethanolamine and unreacted methyl esters. The results of the corrosion experiments show that the product obtained exhibited appreciably high performance as reflected by a percentage of protection (%P) of 96.85%. The performance of the product as a corrosion inhibitor is also supported by the SEM image of the mild steel sample, which shows that the surface of the sample is well protected. The results of this work demonstrate that nitrogen compounds obtained have promising potential as corrosion inhibitors, particularly to prevent corrosion by CO2 gas.